Modelagem estrutural computadorizada de taurina e seus derivados - Henrique, Simone Cabral Monteiro (2021)
Molecular modeling of taurine (TAU), homotaurine (HOTAU) and glyciltaurine (GLYTAU) with a good approximation confirmed the structural data previously obtained by the X-ray technique for these compounds, thus confirming the suitability of the Spartan program to perform calculations with two amino acids and a dipeptide containing sulfonic radical SO3H.The calculation of bond lengths and bond angles provided new structural information on TAU, HOTAU and GLYTAU in which selenium and tellurium were substituted for sulfur of the functional group. Common abbreviation for chalcogens S, Se and Te is Ch. The calculated bond lengths and bond angles of TAU and its derivatives with heavy chalcogens (Se, Te) were found to be similar, except for the remarkable elongation of the key distances Ch-O, Ch-O and Ch-C in proportion to the ionic radii of the substutents. The cumulative effect of such changes may result in significant structural alterations in the entire molecule, leading to promising drugs. It is assumed that the broader spectrum of clinical effects of HOTAU is associated with the existence of conformational isomers with slightly different values of potential energy. In this way, computerized modeling of virtual compounds will be able to provide insights minto the viability of further laboratory synthesis and bioactivity tests.